A comparative in vitro toxicity assessment of electronic vaping product e-liquids and aerosols with tobacco cigarette smoke. (August 2020) - Wieczorek, R.; Phillips, G.; Czekala, L.; Trelles Sticken, E.; O'Connell, G.; Simms, L.; Rudd, K.; Stevenson, M.; Walele, T.
Abstract: The use of electronic vaping products (EVPs) continues to increase worldwide among adult smokers in parallel with accumulating information on their potential toxicity and relative safety compared to tobacco smoke. At this time, in vitro assessments of many widely available EVPs are limited. In this study, an in vitro battery of established assays was used to examine the cytotoxic (Neutral red uptake), genotoxic ( In vitro micronucleus) and mutagenic (Bacterial reverse mutation) responses of two commercial EVPs (blu GO™ disposable and blu PLUS+™ rechargeable) when compared to smoke from a reference cigarette (3R4F). In total, 12 commercial products were tested as e-liquids and as aerosols. In addition, two experimental base liquids containing 1.2% and 2.4% nicotine were also assessed to determine the effect of flavour and nicotine on all three assays. In the bacterial reverse mutation (Ames) and in vitro micronucleus (IVM) assays, exposures to e-liquids and EVP aerosols, with and without nicotine and in a range of flavourings, showed no mutagenic or genotoxic effects compared to tobacco smoke. The neutral red uptake (NRU) assay showed significantly reduced cytotoxicity ( P < .05) for whole undiluted EVP aerosols compared to tobacco smoke, which by contrast was markedly cytotoxic even when diluted. The reduced in vitro toxicological responses of the EVPs add to the increasing body of scientific weight-of-evidence supporting the role of high-quality EVPs as a harm reduction tool for adult smokers. Highlights: Significantly reduced cytotoxicity of EVP aerosols compared to tobacco smoke. No genotoxicity effect of e-liquids or EVP aerosols. No mutagenic effects of e-liquids or EVP aerosols.